Drivers of ASCAT C band backscatter variability in the dry snow zone of Antarctica - Alexander Fraser; Nigro, MA; Ligtenberg, SRM; Benoit Legresy; Mana Inoue; Cassano, JJ; Kuipers Munneke, P; Lenaerts, JTM; Neal Young; Adam Treverrow; van den Broeke, M; Enomoto, H (2016)
C band backscatter parameters contain information about the upper snowpack/firn in the dry snow zone. The wide incidence angle diversity of the Advanced Scatterometer (ASCAT) gives unprecedented characterisation of backscatter anisotropy, revealing the backscatter response to climatic forcing. The A (isotropic component) and M 2 (bi-sinusoidal azimuth anisotropy) parameters are investigated here, in conjunction with data from atmospheric and snowpack models, to identify the backscatter response to surface forcing parameters (wind speed and persistence, precipitation, surface temperature, density and grain size). The long-term mean A parameter is successfully recreated with a regression using these drivers, indicating strong links between the A parameter and precipitation on long timescales. While the ASCAT time series is too short to determine which factors drive observed trends, factors influencing the seasonal and short timescale variability are revealed. On these timescales, A strongly responds to the propagation of surface temperature cycles/anomalies downward through the firn, via direct modulation of the dielectric constant. The influence of precipitation on A is small at shorter timescales. The M 2 parameter is controlled by wind speed and persistence, through modification of monodirectionally-aligned surface roughness. This variability indicates that throughout much of coastal Antarctica, a microwave ‘snapshot’ is generally not representative of longer-term conditions.